The Native Language Factor in Simultaneous Interpretation in an Arabic/English Context - Al-Salman, Saleh; Al-Khanji, Raja’i (Meta, 2002)
AbstractThe present research sought evidence to either support or refute the claim that simultaneous interpreters are more efficient when decoding/interpreting oral discourse from a foreign language into their mother tongue. The data for the study were collected by means of (1) a questionnaire which elicited the responses of a number of professional interpreters who participated in national, regional, and international conferences, and (2) an analysis of the actual performance of some professional interpreters in actual interpretation tasks conducted in both languages. Their performance was analyzed according to some major criteria of linguistic adequacy, strategic competence, and communication strategies. A theoretical framework based on the variability model (Labov 1969) was employed to validate the data.